Knowledge, attitudes and perceptions of a patient population on the COVID-19 vaccine rollout - Makaira Purasram; Varsha Bangalee; Frasia Oosthuizen; Rajatheran Moodley (AOSIS, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has had dire effects on South Africa. Vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are critical in the fight against COVID-19. This study is necessary to optimise vaccine acceptance. Aim: To determine the knowledge, attitudes and perceptions of a patient population in South Africa on the COVID-19 vaccine rollout. Setting: This study was conducted via a retail pharmacy in Merebank, Wentworth and Bluff (Ward 68), which is in the eThekwini Metropolitan Municipality in the KwaZulu-Natal province. Methods: A quantitative study was conducted using an online self-administered questionnaire between April 2021 to September 2021. There were a total of 430 participants. Data were collected on Google Forms, recorded in Microsoft Excel and analysed using descriptive and inferential statistics. Results: Knowledge of COVID-19 in the population was 81.86%. A total of 65% of participants stated that they would definitely take the COVID-19 vaccine, and 33.7% stated that they were hesitant to receive the vaccine. Reasons for hesitancies included concerns surrounding side effects of the vaccines, its safety and efficacy and the fast-tracking of the vaccine. Conclusion: Education campaigns need to be customised to provide the population with reliable and vetted vaccine information and address specific concerns or hesitancies present. Health care workers and the government need to work with religious leaders to improve public trust and confidence in the vaccine. To reach herd immunity and prevent increased morbidity rates, there needs to be a rise in vaccine acceptance across South Africa and globally. Contribution: With the intention of ensuring a successful COVID-19 vaccine rollout strategy in South Africa, it is of great importance to address the reasons for vaccine hesitancy and to determine the knowledge, attitudes and perceptions of the population on the COVID-19 vaccines. This study will therefore aid in developing strategies aimed at improving vaccine education and awareness, thereby resulting in a greater uptake of the COVID-19 vaccine by the population.